20=-4(x-2)-12

Simple and best practice solution for 20=-4(x-2)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20=-4(x-2)-12 equation:


Simplifying
20 = -4(x + -2) + -12

Reorder the terms:
20 = -4(-2 + x) + -12
20 = (-2 * -4 + x * -4) + -12
20 = (8 + -4x) + -12

Reorder the terms:
20 = 8 + -12 + -4x

Combine like terms: 8 + -12 = -4
20 = -4 + -4x

Solving
20 = -4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
20 + 4x = -4 + -4x + 4x

Combine like terms: -4x + 4x = 0
20 + 4x = -4 + 0
20 + 4x = -4

Add '-20' to each side of the equation.
20 + -20 + 4x = -4 + -20

Combine like terms: 20 + -20 = 0
0 + 4x = -4 + -20
4x = -4 + -20

Combine like terms: -4 + -20 = -24
4x = -24

Divide each side by '4'.
x = -6

Simplifying
x = -6

See similar equations:

| -5x-8y=-15 | | 4+5b=6b-3+2+11 | | (3t^2-t-2)(2t^2+3t-1)= | | -3x+39=36 | | -6-4(-3x+10)=-88 | | 7y=2x+5x | | (3-2z)(3+2z)=0 | | 9x-13=5(x+2) | | 4(y-1)+3(y+2)=5(y-1) | | (3x+7)2=36 | | 2x+11y=44 | | 8-4z=11-(3z+5) | | 4y+4=3y-20 | | 3-3v=v-13 | | (9x+7)-(-2x+8)=0 | | 6x+13=8x-29 | | 15+n=1-2n-7 | | -(3y+5)=46 | | 1+2a=-11+7a-7a | | (x)=3-2x | | 8x-10=-14 | | 11(p+29)=759 | | -7z+10z+-19=-1 | | y=3.2x+9.6 | | 8=3(p-9)-10 | | p-29=759(11) | | (2x^4y)(-7x^6y^5)=0 | | K^4+8k^2+15=0 | | 6x+2(2x-17)=66 | | 8x-6=6x+4x | | vi=vf(axt) | | ks+m=m-d |

Equations solver categories